Exploring challenges in PhD studies: a case of science student - Zainal Abiddin, Norhasni (Minda Masagi Press, 2008)
PhD students have to take responsibility managing their own learning and getting a PhD. They are also responsible for determining what is required as well as for carrying it out, and must always keep in touch in regular meetings with the supervisor. The student is the main person responsible for his/her PhD research. Doing a PhD clearly indicates that this is a student’s own research and work. The objective of this research is to provide better guidelines for effective roles of a PhD science student, especially the foreign student. The actual research to be reported used the case study method. Three Malaysian PhD students from three major disciplines of study i.e. arts, science and social science, were interviewed in depth several times within a year. All three case studies would make the present article too long. Therefore, only one case study which focusing on science student will be presented in this article in order to achieve a better understanding of the story. As a result, the research had developed the best effective guidelines in order for students to success in their study.